Machine learning an algorithmic perspective - Marsland, Stephen (Chapman & Hall/CRC machine learning & pattern recognition series, 2015)
Remedying this deficiency, Machine Learning: An Algorithmic Perspective, Second Edition helps students understand the algorithms of machine learning. It puts them on a path toward mastering the relevant mathematics and statistics as well as the necessary programming and experimentation